The Role of Food Processing in Sustaining Food Security Indicators in the Kingdom of Saudi Arabia - Fahad Abdelaziz Almohaimeed; Khaled Ahmed Abouelnour (Economies)
This research aims to explain the role of food processing in improving the sustainability of food security under the framework of ‘Goal 2’ associated with the Sustainable Development Goals (SDGs). The research methodology relied on descriptive and quantitative analysis methods, where the VAR model was used. The key findings reveal that food manufacturing reduces malnutrition rates and increases the level of exports and capital investment, contributing to enhancing the level of sustainability of food security in the Kingdom of Saudi Arabia (KSA). Increasing food production reduces the prevalence of severe food insecurity. Malnutrition in the KSA is not due to a shortage in production of food quantities; rather, it is due to the consumption pattern of the population, and unhealthy food habits and traditions. The food production index does not cause a difference between exports and imports, as there is no dependence of imports and exports on food production. Likewise, the food production index does not cause a change in the value of capital investment in food and beverage factories. The increase in food production and, investment in food processing, and the decrease in the difference between food imports and exports by 10% for one lag period led to a decrease in the proportion of malnourished people in the total population by about 0.25%, 1.7%, and 1.33%, respectively. Moreover, these variables led to a decline in the prevalence of severe food insecurity by 0.3%, 0.66%, and 0.4%, respectively, and led to an increase in the food production index by 1.62. The study recommends that more emphasis should be given to increasing food processing and encourages local and foreign investment in this area to maintain sustainable food security indicators in the KSA.